Pendidikan Islam Di Era Globalisasi : Peluang Dan Tantangan - Hasanah, Muwahidah Nur (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2017)
Advances in science and technology is the result of human cultivation must be coordinated in order to comply with national identity, noble values, traditions, culture, and religion. Global phenomenon can not be avoided, processes, dynamics and its influence has been successfully castrated traditions and noble values of religious Muslims today. Educational values of Islam today is getting late in the tumult of various changes that are the result of the influence of globalization. Globalization has become a historical necessity that many challenges (threat) also opportunities (opportunity) in education that will shake up the order of the culture, customs, and values of the noble teachings of Islam. Therefore reformatting the theory and practice of education should be carried out and balanced, so that Islamic education is not passive as a spectator instead of a player, as consumers rather than producers. Islamic education also must perform and portray themselves as agents of change while strengthening Islamic identity. For the creation of a Muslim who is not only a knowledge of general (or vice versa), but also excels in the science of religion, so that it can perform with good mobility and orderly life. The position of Islamic education is compulsory maintain selective, critical, and open to the emergence of globalization. In addition, it should also remain consistent with the main source of religion, namely the Qur'an and Hadith while expanding the knowledge and understanding of the progress of time, modernity, the findings of science and technology